2014
DOI: 10.3390/ma7020653
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Multifunctional Fe@Au Core-Shell Nanoparticles with Surface Grafting as a Potential Treatment for Magnetic Hyperthermia

Abstract: Iron core gold shell nanoparticles grafted with Methotrexate (MTX) and indocyanine green (ICG) were synthesized for the first time in this study, and preliminarily evaluated for their potential in magnetic hyperthermia treatment. The core-shell Fe@Au nanoparticles were prepared via the microemulsion process and then grafted with MTX and ICG using hydrolyzed poly(styrene-alt-maleic acid) (PSMA) to obtain core-shell Fe@Au-PSMA-ICG/MTX nanoparticles. MTX is an anti-cancer therapeutic, and ICG is a fluorescent dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…The 2θ peaks at 38.67°, 44.81°, 64.4°, and 77.96° highlighted the (111), (200), (220), and (311) planes of face‐centered cubic (FCC) gold particles while the 2θ peaks at 43.9° and 64.8° highlighted the body‐centered cubic (BCC) planes of iron particles (Figure C). These results are consistent with those of our previous studies and other research groups, which indicates the presence of Fe and Au. To analyze the composition of each oFe@Au Np further, energy dispersive X‐ray spectroscopy (EDS) (Figure D) and inductively coupled plasma mass spectroscopy (ICP‐MS) were performed.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The 2θ peaks at 38.67°, 44.81°, 64.4°, and 77.96° highlighted the (111), (200), (220), and (311) planes of face‐centered cubic (FCC) gold particles while the 2θ peaks at 43.9° and 64.8° highlighted the body‐centered cubic (BCC) planes of iron particles (Figure C). These results are consistent with those of our previous studies and other research groups, which indicates the presence of Fe and Au. To analyze the composition of each oFe@Au Np further, energy dispersive X‐ray spectroscopy (EDS) (Figure D) and inductively coupled plasma mass spectroscopy (ICP‐MS) were performed.…”
Section: Resultssupporting
confidence: 94%
“…To establish the potential of the oFe@Au‐MTX conjugate to be used as a drug‐releasing platform upon photo‐stimulation, oFe@Au‐MTX drug‐nanoparticle conjugates were exposed to laser light for different periods and the amount of MTX released was quantified using UV–vis spectroscopy. MTX usually shows a distant absorption peak at 304 nm, as observed in our previous studies . The presence of a distinct absorption peak at 304 nm in this study also indicated the presence of MTX.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This can be achieved by combining two or more metal components into a single alloy or core-shell nanoparticle 2 3 . For biomedical applications, the gold-iron system is particularly interesting 4 5 6 7 . In this context, iron-based particles are relevant because of their magnetic properties that are applicable for magnetic resonance imaging (MRI) 8 and thermotherapy 9 , whereas gold is a promising material for its oxidation resistance, optical properties 10 , and ability to be easily functionalized by thiolated biomolecules 11 .…”
mentioning
confidence: 99%
“…MNPs show potential biomedical applications, such as localized cellular therapy, magnetically-guided drug delivery, magnetic resonance imaging (MRI), hyperthermia treatment, and magnetofection on the interaction with an external magnetic field [ 1 , 2 ]. Among MNPs, metallic iron nanoparticles (Fe NPs) have been studied and applied in the research fields of optics, catalysis, magnetism and biomedicine for years [ 3 , 4 , 5 ]. One benefit to prepare metallic iron NPs is that FeNPs have a much stronger shortening effect on T 2 relaxation time than iron oxide nanoparticles (IONPs), suggesting that FeNPs may be more effective MRI contrast agents [ 3 ].…”
Section: Introductionmentioning
confidence: 99%